The Strengthening of Democracy in a Law State - Lalu, Nikson Gans; Pieris, John; Simatupang, Dian Puji N; Hardjono, (Advances in Social Sciences Research Journal, 2023)
Democracy as a system of people's government is not limited to how to choose a leader, but the way he leads the government must be in accordance with his people's commitment. Democracy is not just a process but has norms that animate the life of the nation and state. Practicing democracy means that people must be free from fear and have the integrity to be able to work together based on equal rights. Democracy can develop if there are civil liberties that are oriented to the public interest. The desired freedom is civil freedom that gives birth to civic culture to strengthen and enhance the quality of democracy. Civil liberties foster citizen participation within the framework of demos, namely inclusive political identity as fellow citizens of this nation. Demos consolidation needs to be proven by opening space for substantial democratic consolidation. In line with this, civil society continues to contribute to building deliberative democracy. The practice of democracy in Indonesia needs to be reoriented, the vision shifted to make room for the grassroots to express their aspirations. This idea is not just a counter-discourse, but to seek alternative praxis. Democracy is also a political method of organizing state institutions by state administrators. Because of this, the idea emerged that the way to limit government power must be through the Constitution. Executive power must be balanced by legislative power. This is what is called constitutionalism. The Indonesian legal state based on Pancasila adopts a prismatic concept to look for the good aspects of the legal tradition of civil law and common law. For Indonesia, democracy must refer to the principle of constitutionalism which limits power and prevents the tyranny of the majority.